German in 3 months your essential guide to understanding and speaking German - Martin, Sigrid-B (New York, NY DK Publishing, 2022)
"Everything you need to understand and speak German. Free audio app helps you perfect your pronunciation by imitating native speakers. Builds vocabulary through word lists, key phrases, and model sentences. Explains essential grammar. Develops conversation through exercises based on real-life scenarios"--Back cover
"Free audio app."
Includes index
Keywords: German language -- Problems, exercises, etc; German language -- Textbooks for foreign speakers -- English; German language -- Self-instruction; German language; Problems and exercises; Self-instruction; Textbooks -- for English speakers